Association of Neurotensin Receptor 1 Gene Polymorphisms With Defense Mechanisms in Healthy Chinese - Ma, Hui; Li, Min; Zhang, Liguo; Tao, Jiangang; Zhu, Gang (Frontiers in Psychiatry, 2021)
Aims: In the central nerve system, neurotensin (NT), and neurotensin receptor 1 (NTR1) modulate the dopamine system. Gene variations in the dopamine system have been demonstrated to influence certain defense mechanisms, but no studies have investigated possible effect of NTR1 gene polymorphisms in the biological determination of these defenses. The present study therefore examined this link. Methods: In 412 healthy Han Chinese, single nucleotide polymorphisms rs6090453C/G, rs6011914C/G, and rs2427422A/G of the NTR1 gene were genotyped, and the defense mechanisms were measured by the self-reporting Defense Style Questionnaire 88. Results: Significant male-specific differences in the projective identification among the rs6090453 genotypes (p = 0.003); in the intermediate defense, reaction formation, and projective identification among the rs6011914 genotypes (p = 0.011, 0.010, and 0.011, respectively); and in the projective identification among the rs2427422 genotypes (p = 0.005) were found when the level of significance was adjusted by the Bonferroni correction. There was no significant difference in any of the defense scores among genotypes of any single nucleotide polymorphism in the total cohort or female subjects (all p > 0.017). The distributions of genotypes between the low and high score subgroups showed significant differences in the rs2427422 genotype distributions for help-rejecting complaining, regression, and projective identification (p = 0.010, 0.022, and 0.044, respectively). Significant differences were found between males and females in 10 defense mechanisms (all P < 0.05). Conclusions: The gene variations in the NTR1 polymorphisms were involved in the biological mechanisms of intermediate defense mechanisms, and this effect was influenced by sex.